(untitled) (Fiep Bulletin - online, 2015)
Low limb power is one of the most important requirements for a great performance in volleyball. Therefore, the importance of ergogenics use to increase anaerobic power is observed. Objective: Verify if creatine and maltodextrine supplementation, with low doses (5g and 30g respectively) and short-duration (7days), has positive effects on anaerobic performance. Method: Seven college athletes were recruited from the volleyball team of Federal University of Parana. Anthropometrics measures (body mass, height and body fat percentage), Absolute Peak Power (APP) and Relative Peak Power (RPP) during Wingate test were evaluated. After this, two groups were created, a supplementation group (SG) composed by 4 subjects and a control group (CG) with 3 subjects. The subjects were instructed to maintain the same habitual training and food intake. After the last day supplementation, all tests were repeated. The values were analyzed by the Mann Whitney test (comparisons between groups) and Wilcoxon test (comparisons between pre and post-test conditions). The significance level was set at p<0.05. Results: No significant differences were found in any of the study variables, neither in comparisons between groups nor in pre and post-test conditions. Conclusion: We conclude that the low-dose, short-term creatine and maltodextrine supplementation did not influence the Absolute and Relative Peak Power of the volleyball athletes during the Wingate test.